APLIKASI TEKNOLOGI BUDIDAYA TANAMAN PAKAN RAMAH LINGKUNGAN TERHADAP KUALITAS HIJAUAN (Studi Pemanfaatan Pupuk Organik Kascing dan Sistem Tanam) - Suarna, I Wayan (Bumi Lestari, 2012)
Chemical analysis of forages was conducted at Animal nutrition Laboratory, Faculty of Animal Husbandry Udayana University to study the effect of casting organic fertilizer on Quality in Grass-legume Association. Field experiment was consisted of two factors as follows: (1) three types of cropping systems (grass monoculture, legume monoculture, and grass-legume association), (2) four levels of casting organic fertilizer (0, 10, 20, and 30 t ha-1). The experiment design was a randomized block design arranged in factorial pattern and was replicated three times. The results showed chemical compossition of forage in association system at 20 t ha-1 casting had a higher quality and a higher Ca and P contents, a lower NDF and lignin contents, whereas : ADF, hemisellulose, and cellulose contents were not significantly different.
Keywords: Casting, Cropping System, and Forage Quality.